DENSITIES AND ELECTRICAL CONDUCTIVITIES OF COPPER(II) CHLORIDE SOLUTIONS IN DIMETHYL SULFOXIDE AND WATER–DIMETHYL SULFOXIDE EQUIMOLAR MIXTURE AT THE TEMPERATURES 298.15 K, 308.15 K AND 318.15 K (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
Densities and electrical conductivities for copper(II) chloride solutions in DMSO and water–DMSO equimolar mixture have been measured at different temperatures. Apparent molar volumes, partial molar volumes and transfer molar volumes of the solvated copper(II) cations were derived and interpreted in terms of ion-solvent interactions. The ligand-field and temperature effects on the partial molar volumes and electrical conductivities were discussed as well.
Keywords: density, electrical conductivity, copper(II) chloride, dimetyl sulfoxide; apparent, limiting partial, transfer partial molar volumes